Diagnosis and Management of Splenic Torsion in a Cane Corso Dog - Divya Dharshini, S.; S.Kavitha; K.Jeyaraja; V.Vijayanand; M.Bharathidasan (The Indian Veterinary Journal, 2026)
Splenic torsion is a life-threatening acute abdomen disorder in dogs. A four-year-old female Cane Corso dog was presented to the Madras Veterinary College Teaching Hospital with a history of abdominal pain, vomiting, inappetence and lethargy in the last three days. Physical examination revealed splenomegaly, and abdominal ultrasonography showed marked splenic enlargement with a lacy parenchymal pattern, suggestive of splenic torsion. Molecular technique revealed the presence of the Babesia species. The animal was stabilised with emergency medical management with blood transfusion and treated for babesiosis. Subsequently, an exploratory laparotomy was performed for splenectomy. The animal recovered eventually.